Method for forming a surface finish on an electrically conductive substrate and electrical conductor having a surface finish - Patents.com

The method of using gravure or flexographic printing to apply and heat conductive ink on substrates addresses the cost and reliability issues of existing surface finish technologies, resulting in a robust and cost-effective surface finish with reduced whisker formation.

JP7646993B2Active Publication Date: 2025-03-18TE CONNECTIVITY GERMANY GMBH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023101299
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-21
Publication Date
2025-03-18
Estimated Expiration
2043-06-21

AI Technical Summary

Technical Problem

Existing methods for forming surface finishes on conductive substrates are costly and prone to issues such as whisker formation and surface damage due to oxidation.

Method used

A method involving gravure printing or flexographic printing to transfer an ink containing conductive particles onto a conductive substrate, followed by heating the ink above its melting point to form a reliable surface finish, which can include intermetallic layers for enhanced adhesion and whisker prevention.

Benefits of technology

This method provides a cost-effective and reliable surface finish with improved adhesion and reduced whisker formation, ensuring the integrity of the surface finish and enhancing the electrical conductor's performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007646993000001
    Figure 0007646993000001
  • Figure 0007646993000002
    Figure 0007646993000002
  • Figure 0007646993000003
    Figure 0007646993000003
Patent Text Reader

Abstract

To provide a cost-efficient method for producing a reliable surface finish on an electrically conductive substrate, as well as to provide an electric conductor.SOLUTION: The invention relates to a method for producing a surface finish (20) on an electrically conductive substrate (2), the method comprising the steps of transferring an ink (6) comprising electrically conductive particles (8) onto an area (20) of predetermined form and / or size on a surface (4) of the electrically conductive substrate (2) via gravure and / or flexo printing and heating the ink (6) to a temperature that is higher than a melting point of the conductive particles (8) to create a melt, which solidifies into the surface finish (20). Furthermore, the invention relates to an electric conductor (1) comprising an electrically conductive substrate (2) having a surface (4) with an area (10) of predetermined size and / or form on which a surface finish (20) is applied with the aforementioned method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION The present invention relates to a method for producing a surface finish on an electrically conductive substrate, and more particularly to an electrical conductor comprising an electrically conductive substrate having a surface finish. [Background technology]

[0002] Electrical conductors are used in a variety of applications to form electrical connections with mating conductors. Electrical conductors comprise a conductive substrate, such as copper or a copper alloy, for transmitting electricity. Surface finishes are applied to the electrical contacts to facilitate movement during connection and to prevent surface damage from oxidation and other causes. Traditionally, surface finishes are applied to the conductive substrate using electroplating, electroless plating, physical vapor deposition, or hot-dip plating. These processes are expensive and / or tin-based surface finishes are prone to whisker formation. Summary of the Invention [Problem to be solved by the invention]

[0003] It is therefore an object of the present invention to provide a more cost-effective method for producing a reliable surface finish on a conductive substrate and to provide a cost-effective electrical conductor having a reliable surface finish. [Means for solving the problem]

[0004] The above problems are solved by a method for forming a surface finish on a conductive substrate, the method comprising the steps of transferring an ink containing conductive particles to an area of ​​a predetermined shape and / or size on the surface of the conductive substrate by gravure printing and / or flexographic printing, and heating the ink to a temperature above the melting point of the ink to produce a melt which solidifies into the surface finish.

[0005] The above problem is further solved by an electrical conductor comprising a conductive substrate, the conductive substrate having a surface including an area of ​​a predetermined shape and / or size that has been surface finished by the above method.

[0006] According to the above solutions, ink is applied to the area by gravure and / or flexography. The gravure printing process uses a cylinder with engraved cells on its surface, also called engravings. These engravings can be filled with ink and the excess can be removed by a doctor blade. These engravings can have patterns which can be square, rectangular, oval, circular, striped, etc., helping to save material and can be custom designed for the product. The ink from the cells is then transferred to the substrate. Gravure printing has significant advantages over other printing processes in terms of transferring the ink to the substrate. Gravure printing excels in speed, variable ink film thickness to be laid down, long runs of the press, and the simplicity of the process involved in transferring the ink to the substrate. Furthermore, large areas of ink can be transferred at high speeds with nominal distortion, therefore, gravure printing offers a cost-effective solution compared to traditional methods for creating surface finishes on conductive substrates.

[0007] In flexographic printing (also called flexo printing), artwork is designed based on the desired final print of an anilox roll similar to gravure printing. Instead of an anilox roll transferring ink directly to the substrate as in gravure printing, the anilox roll for flexographic printing transfers ink to an image carrier, which transfers the image to the substrate. Flexographic presses pull the substrate between the image carrier and the image cylinder. The rolling design of flexographic printing helps achieve high speeds and allows for large print runs similar to gravure printing.

[0008] Gravure printing is particularly advantageous compared to other known printing processes such as screen printing and inkjet. For example, the resolution of screen printing is limited by the mesh screen through which the ink paste is forced. Furthermore, screen printing cannot provide thin layers less than 5 microns. These processes also lack the speed of gravure printing. Furthermore, the materials used in inkjet printing are not economical. Due to the small nozzle orifices of the inkjet printhead, small particles (e.g., less than 1 micron) must be used to prepare the ink, typically nanoparticle ink, which is very expensive.

[0009] Melting the ink that solidifies into the surface finish allows the ink to reflow and adhere to the substrate, in some embodiments, through the formation of an intermetallic layer between the conductive substrate and the surface finish. Thus, the integrity of the surface finish is ensured and prevents the surface finish from being removed from the substrate, for example, by wiping. Additionally, the reflow of the ink and / or the presence of any organic binder in the surface finish can mitigate whisker formation.

[0010] The surface finishes formed by the above methods have a unique topography with a grain-like structure, and thus can be detected, for example, by scanning electron microscope (SEM) images of both the top and cross sections.

[0011] The invention can be further improved by the following mechanisms, which are independent of one another in terms of their respective technical effects and which can be combined in any way:

[0012] For example, after the ink has been transferred to an area of ​​a predetermined shape and / or size, the ink can be heated to a temperature above the inherent melting point of the ink, particularly the conductive particles of the ink.

[0013] The substrate may in particular be a copper substrate, where the term "copper" includes pure copper and copper alloys.

[0014] According to one particularly advantageous embodiment, the ink can be indirectly heated by inductively heating the conductive substrate. Compared to other heating methods such as infrared heating, hot air heating, or reflow heating under N2, the integrity of the surface finish when heated by induction heating is much better. Eddy currents flow against the electrical resistance of the conductive particles and / or the conductive substrate, e.g., a Cu substrate, generating precise and localized heat in the substrate, which then indirectly heats and melts the conductive particles of the ink. Heating the substrate as well as the ink further improves the bonding of the finish to the substrate, e.g., by forming intermetallic compounds during the heating process. The integrity of the surface finish can be determined by testing the adhesion of the ink to the substrate using cellophane tape and cleaning with isopropyl alcohol.

[0015] The main advantage of heating the ink by induction is that eddy currents are generated in the conductive substrate, which heats the ink from below. Thus, the ink starts to melt from the bottom toward the top. By adjusting the time exposure and current of the induction heater, the properties of the melt and / or the surface finish can be varied, which increases the versatility of the surface finish produced by the method. The dwell time for this process can be from 0.5 seconds to 5 seconds, and also depends on the coil geometry. In some embodiments, a constant current is applied to the induction heating coil to heat the conductive ink. In other embodiments, a stepped current, such as a high-low-high current profile or a high-low-low profile, is applied to the induction heating coil. In further embodiments, pulsed currents are applied to the induction heating coil, for example, 5 second pulses spaced 5 seconds apart for a total of four pulses, or 3 second pulses spaced 5 seconds apart for a total of five pulses. The combination of different currents, pulse lengths, and intervals ensures a more uniform temperature profile and avoids overheating the substrate. In some cases, the distance between the coil and the substrate, as well as the speed at which the substrate moves between the coils, can improve and affect the uniformity of the finish. The substrate can be placed directly on the coil, i.e., at a distance of 0 mm, or at a distance of up to 15 mm. In one embodiment, the distance between the substrate and the coil can be 0 mm to 15 mm. The speed of movement can be 1 m / min to 60 m / min.

[0016] For example, a layered structure can be formed in an area of ​​a given size and shape having at least one layer that includes or is composed of an intermetallic phase and a layer of solid conductive particles, the intermetallic phase providing a strong bond between the conductive substrate and the surface finish.

[0017] Preferably, an intermetallic phase is formed at the interface of the conductive substrate. Preferably, a layer of solid conductive particles forms the top layer of the surface finish. The top layer is defined as the layer facing away from the surface of the conductive substrate in the area. The solid conductive particles forming the top layer of the surface finish can increase the coefficient of friction. This is particularly advantageous for crimping applications as it can prevent slippage. Less than 50% of the ink, preferably 20-40%, can form an intermetallic phase in the solidified surface finish. The remainder of the ink can form a layer of solid conductive particles.

[0018] The electrical conductor may be, for example, a crimp terminal having a crimp area for attaching the terminal to a mating conductor, where a surface finish may be applied to the crimp area.

[0019] In a particularly advantageous embodiment, the ink is not heated by the electron beam. The electron beam has a very high kinetic energy, which is converted into heat and melts the conductive particles of the ink. However, the electron beam also generates high thermal stresses, especially when the heated area is large, which can cause deformation of the substrate. Furthermore, electron beam melting is subject to high material losses due to ablation and / or evaporation.

[0020] The conductive particles of the ink may preferably include or consist of tin. The term "tin" refers to pure tin and / or tin alloys such as SAC, a tin-silver-copper alloy. The tin alloy may have, for example, a tin content of about 96.5 wt%, a silver content of about 3.5 wt%, and a copper content of about 0.5 wt%. Tin surface finishes are very reliable for protecting substrates from corrosion and establishing electrical interconnections between conductors and mating conductors at low cost. The use of the above method for tin finishing is particularly advantageous as it provides cost savings of up to 65% compared to the cost of hot-dip Sn finishes.

[0021] If the conductive particles of the ink contain or consist of tin, it is advantageous that the ink, and in particular the conductive particles, are not melted by electron beam melting. Tin has a high vapor pressure and therefore causes explosive evaporation when heated by the electron gun. This leads to contamination of the vacuum chamber and frequent loss of vacuum.

[0022] The conductive particles of the ink are preferably melted by inductive heating to allow for fast and efficient melting with low thermal stress, particularly when the conductive particles include or consist of tin.

[0023] Some applications require different surface finishes in different areas of the electrical conductor, so that each area is optimized for its own task. Thus, a first set of conductive particles, i.e. conductive particles of an ink, may be gravure-printed and / or flexographically printed in a first area of ​​a predefined shape and / or size, and a second set of conductive particles may be transferred to a second area of ​​a predefined shape and / or size. In this case, the material of the first set of conductive particles and the material of the second set of conductive particles may be different from each other. Furthermore, the first and second areas may be different from each other, in particular they may not overlap.

[0024] The second set of conductive particles can be transferred to the second region by any suitable means. The transfer of the second set of conductive particles to the second region is not limited to by gravure printing. The second set of conductive particles may be included in a second ink, which is printed to the second region by any known printing means. However, gravure printing and / or flexographic printing are preferred for the advantages mentioned at the beginning.

[0025] Preferably, the first and second inks are transferred to their respective regions in a single process step, or, in the best case, the first and second inks are transferred simultaneously, further reducing the overall build time.

[0026] The second set of conductive particles may comprise or consist of silver. Silver is particularly suitable for high frequency applications having good electrical conductivity. The second region is therefore preferably located in a contact area of ​​a releasable electrical connection such as a plug connection. The first region may be located in an attachment area such as a crimp area of ​​an electrical conductor. Such attachment areas often undergo plastic deformation in order to be secured to a mating conductor and form an electrical connection with the mating conductor.

[0027] The first set of conductive particles and the second set of conductive particles are preferably melted in a subsequent processing step. The second set of conductive particles can be melted after the first set of conductive particles. The second set of conductive particles can be melted, for example, by electron beam melting.

[0028] Tin has a much lower melting point than silver. Thus, for example, in a first step, tin can be melted by induction heating, which can also serve as a drying step for the second ink. The silver can then be melted by electron beam melting. The first step by induction heating can also help improve the adhesion of the second ink, reducing ablation of the second ink during the subsequent electron beam step of the second ink. The surface area of ​​the first region can be larger than the second region. In particular, the surface area of ​​the first region can be at least twice the surface area of ​​the second region.

[0029] Gravure printing and flexographic printing, as well as the combination of both, can achieve high resolution. Thus, the electrical conductor can include a surface finish with particularly high resolution. For example, the lateral resolution of the edge of the surface finish can be less than about 1 mm, particularly less than about 0.2 mm. The lateral resolution is defined as the smallest distance at which two points can be individually distinguished. Thus, a small lateral resolution allows the distinction of two separate objects adjacent to each other, namely the surface finish and the surface of the substrate.

[0030] Moreover, the above methods are versatile and can be used to customize surface finishes with high precision according to application requirements. Thus, the surface finish can have a predetermined thickness variation within an area as well as a specific surface structure and / or pattern.

[0031] The ink may comprise several components, in particular a binder, a dispersant, a solvent and conductive particles. By "melting the ink" it is understood that at least a portion of the conductive particles melt. Thus, the method may comprise a step of heating the ink to a temperature that melts all the particles, or the method may comprise a step of heating the ink to a temperature that is higher than the inherent melting point of the conductive particles. Other components of the ink may already have evaporated at this melting point.

[0032] Gravure and / or flexographic printing can provide a dense, thin surface finish. The surface finish can have a thickness of, for example, less than 10 times, less than 5 times, or less than 2 times the average diameter of the conductive particles of the ink. The surface finish can have a material thickness of less than about 10 μm, in particular less than about 5 μm. Preferably, the surface finish can have a thickness of about 2 μm to about 10 μm or about 2 μm to about 5 μm.

[0033] For such small surface finish thicknesses, it is advantageous for the conductive particles of the ink to have an average particle size of less than about 25 μm, less than about 10 μm, in particular less than about 5 μm. The average particle size is preferably between 2 μm and about 10 μm or between about 2 μm and about 5 μm.

[0034] In order to obtain a uniform surface finish and improve print quality, it is particularly advantageous for the ink to have a low dynamic viscosity. -1 It is preferred that the kinematic viscosity is less than about 10 Pas (Pa s, PA s) (10,000 cP) measured at 25°C. -1 The ink can be distinguished from solder paste, which has a dynamic viscosity of about 10-25 Pas (10,000-25,000 cP) measured at 25°C. -1 Preferably, the viscosity is less than about 1 Pas (1000 cP) measured at 1000.

[0035] Typically, metal oxides have a relatively high melting point compared to pure metals or metal alloys. For example, the melting point of tin oxide is about 1630°C, while the melting point of pure tin is about 232°C. Therefore, it is particularly advantageous to minimize the oxygen content of the conductive particles in order to optimize the reflow process. The oxygen content may be less than about 1 wt%, less than about 0.8 wt%, less than about 0.5 wt%, less than about 0.3 wt%, less than about 0.2 wt%, or even less than about 0.1 wt%, as determined, for example, by inert gas fusion of elemental analysis.

[0036] Exemplary embodiments of methods for forming a surface finish and electrical conductors are described in more detail below with reference to the accompanying drawings.

[0037] In the drawings, the same reference numerals are used for elements which correspond to one another in terms of function and / or structure.

[0038] According to the description of the various aspects and embodiments, if the technical effect of an element shown in a drawing is not necessary for a particular application, that element may be omitted. Conversely, if the technical effect of a particular element is advantageous for a particular application, an element not shown and not described with reference to a drawing, but previously mentioned, may be added. [Brief description of the drawings]

[0039] [Figure 1] 1 is a schematic flow chart for forming a surface finish on a conductive substrate in accordance with an exemplary embodiment of the present invention. [Diagram 2] FIG. 2 is a top view of an electrical conductor having a surface finish according to an exemplary embodiment of the present invention. [Diagram 3] 1 is a cross-sectional SEM image of the surface finish showing the intermetallic layer and the free Sn layer. [Figure 4] 1 is a top view SEM image showing the particle structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] 1 is a schematic flow chart of a method of forming a surface finish on a conductive substrate. According to an exemplary embodiment, a conductive substrate 2, which may include or consist of copper or a copper alloy, has a surface 4. An ink 6 containing conductive particles 8, in particular tin or tin alloy particles, is transferred to areas 10 of predetermined shape and / or size on the surface 4, in the exemplary embodiment shown, by gravure printing. Alternatively, the ink 6 containing the conductive particles 8 may be transferred by flexography instead of gravure printing, or the ink 6 may be transferred using a combination of gravure and flexography.

[0041] The gravure printing process uses a cylinder 12 with engraved cells 14 on its surface 16. These cells 14 are filled with ink 6 and the excess can be removed by a doctor blade 18. The ink 6 from the cells 14 is then transferred to the substrate 2 by capillary action. Gravure printing has significant advantages over other printing processes for transferring ink to a substrate. Gravure printing excels in speed, variable ink film thickness to be laid down, long press runs, and the simplicity of the process involved in transferring the ink to the substrate. Furthermore, large areas of ink can be transferred at high speeds with limited distortion. Gravure printing therefore offers a cost-effective solution compared to conventional methods for creating a surface finish on conductive substrates.

[0042] Gravure printing is particularly advantageous compared to other known printing processes such as screen printing and inkjet. For example, the resolution of screen printing is limited by the mesh screen through which the ink paste is forced. The resolution of inkjet is too low for applications in electronic systems. These processes also lack the speed of gravure printing. The same advantages apply to embodiments in which the ink 6 is transferred by flexography.

[0043] After the ink has been transferred to the surface, the conductive substrate 2 is transferred to an induction device 19, e.g., an induction oven. In the device 19, the ink is heated by induction heating to a temperature above the inherent melting point of the conductive particles 8. Induction heating is particularly advantageous because the substrate is conductive. This means that eddy currents can be formed in the substrate to heat the ink 6 from below. Heating depends on the coil geometry, heating time, and current. For example, a sufficient reflow result can be obtained by heating at about 5A for about 15s to about 20s with a pancake coil. It should be understood that the heating time can be reduced by using a higher current. Furthermore, the heating time and current can be further adjusted depending on the coil geometry, since the coil geometry determines how efficiently the substrate is heated.

[0044] After melting of the conductive particles 8, components of the ink 6 may evaporate or form a mixture with the melt, which then solidifies into the surface finish 20. Thus, the ink 6 reflows and adheres to the substrate 2. As a result, the integrity of the surface finish is ensured and prevents the surface finish from being removed from the substrate, for example by wiping. Furthermore, reflowing of the ink 6 may mitigate whisker formation.

[0045] At the same time as applying the ink containing conductive particles that contain or consist of tin, a second ink containing a second set of conductive particles of a different material can be transferred to a second area (not shown) of predetermined size and / or shape. The second set of conductive particles can in particular contain or consist of silver. It is understood that silver can mean pure silver or a silver alloy. Silver is particularly suitable for high frequency applications having good electrical conductivity. The second area can therefore be particularly located in the contact area of ​​a releasable electrical connection such as a plug connection.

[0046] The first and second regions may be different and may not overlap. During induction heating, the particles containing and / or consisting of silver may be heated but not melted. However, the induction heating process may provide advantages to the second region, such as reducing the processing time of the second ink and improving the adhesion of the ink to the substrate, thus reducing ablation of the second ink during the subsequent melting process. It is preferred to melt the first set of conductive particles by induction heating before melting the second set of conductive particles in a subsequent processing step. The second set of conductive particles may be melted, for example, by electron beam melting. During electron beam melting, the substrate containing the ink is placed under vacuum and fused through heating by the electron beam. Since the conductive particles containing or consisting of tin have already been reflowed, only the second set of conductive particles, namely the silver particles, need to be melted by the electron beam.

[0047] The electron beam has a very high kinetic energy, which is converted into heat to melt the metal particles of the second ink. Only the silver particles are melted by the electron beam melting, which reduces thermal stresses that can cause deformation of the substrate. In particular, the melting of tin by the electron beam can be avoided. Tin has a much lower melting point than silver and a high vapor pressure, which causes explosive evaporation when heated by the electron gun. This causes contamination of the vacuum chamber and frequent loss of vacuum.

[0048] The quality of the tin surface finish 20 depends on the preparation and processing of the ink 6. Therefore, the surface finish 20 can be adjusted by modifying the ink.

[0049] In particular, the ink 6 can be optimized for viscosity and rheology to allow optimal print quality and uniform print thickness. Printing with solder paste can be performed for 10 s at 25° C. -1 The ink has a kinematic viscosity of more than 10 Pas measured at 25° C. and has been found not to give satisfactory results.-1 Less than 10 Pas measured at 25°C, especially less than 10 s -1 It is preferred that the viscosity is less than 1 Pas measured at 1000.

[0050] Another component of the ink that ensures good wetting is the oxidation level of the tin particles of the ink. Commonly available tin powders have surface oxides. The melting point of tin oxides is significantly higher (1630°C) than pure tin (232°C) and they do not melt by conventional methods. These surface oxides therefore have a negative effect on reflow and wetting properties. Advantageously, the oxygen content of the tin particles can be about 1 wt% or less, about 0.8 wt% or less, less than about 0.5 wt%, less than about 0.3 wt%, less than about 0.2 wt%, or even less than about 0.1 wt%. As a result, the wetting ability of the ink can be further improved.

[0051] Further components of the ink may be organic binders or stabilizers, which are used to disperse the metal particles and adjust the viscosity of the ink. The binder or stabilizer materials may degrade during the induction heating step. In some embodiments, after the induction heating step, the binder and stabilizer materials remain or partially remain, or decomposed components of the binder and stabilizer materials remain. Without being limited by theory, it is believed that these binders and stabilizers or their decomposed components prevent the formation of whiskers.

[0052] Some applications require a thickness of the surface finish 20 of from about 2 μm to about 10 μm, or even from about 2 μm to about 5 μm. To achieve a sufficiently uniform surface finish at such a small thickness, it has been found that the conductive particles containing or consisting of tin have an optimal particle size of less than about 10 μm.

[0053] As the conductive particle size decreases, the total surface area increases, which corresponds to a higher oxide content. Therefore, larger particle size, low oxide content tin or tin alloy powders with average diameters greater than 25 μm are more commonly available. To improve the quality of the surface finish, it is desirable to provide inks that include conductive particles with average diameters less than 10 μm and low oxygen content, particularly less than about 0.1 wt %.

[0054] It is preferred that the conductive particles used in the ink have a narrow particle size distribution. Controlling the particle size distribution to a narrow spectrum allows for more uniform printing with less streaking.

[0055] Different techniques for melting the printed ink were evaluated, including reflow under nitrogen, hot air, infrared heating, and induction heating. The integrity of the finish was determined by testing the adhesion of the ink to the substrate using cellophane tape and cleaning with isopropyl alcohol (IPA). Well-adhered ink will not wipe off when treated with IPA or cellophane tape. Best results were obtained when the print was heated with an induction heater. In one sample, a tin-silver-copper alloy (SAC) ink is printed on a copper alloy as a conductive substrate. The copper alloy may be phosphor bronze. The ink was heated by an induction heater at 5A for 20 seconds. The resulting surface finish had a thickness of 2.29 μm as measured by XRF. XRD analysis of this sample showed multiple phases including Cu, SnO2, and an intermetallic peak of Cu6Sn5 at the interface between the conductive substrate 2 and the tin surface finish 20 indicating a strong bond. FIG. 3 shows a cross-sectional SEM image of the surface finish 20 showing the conductive substrate 2, the intermetallic layer 21, and the layer of solid conductive particles 8 that form the top layer of the surface finish 20.

[0056] FIG. 4 is a top view SEM image showing the formed grain structure on the top surface of the surface finish 20 obtained by the method of the present invention. Hot dip tin and e-beam tin surface finishes have a fairly smooth top surface. These formed grain structures provide an additional unique mechanism of the present invention to impart surface roughness to the surface finish 20. This is particularly useful for crimp terminations. The grain surface imparts surface roughness to the product and exhibits a certain amount of free Sn and some intermetallics. Intermetallics are brittle, while free Sn is soft. Having a unique grain surface with surface irregularities and / or surface roughness allows for a greater amount of plastic deformation during contact. This also allows for a larger contact area. Such particle surfaces therefore provide lower contact resistance and also a lower coefficient of friction. Surface roughness further modifies the mechanical properties of the surface and helps prevent the propagation of microcracks in the surface.

[0057] Further testing was performed to determine wear friction and contact resistance. Caps were punched from the printed coupons, induction heated for 20 seconds, and tested against the same flats to determine the coefficient of friction. The coefficient of friction between the caps and the contact finish was measured up to 100 cycles of back and forth strokes over a 5 mm wear track with a 200 g load. The results showed that the phosphor bronze reflowed SAC ink exhibited a stable wear / friction response. The coefficient of friction stabilized at about 0.5 or 0.7, which is lower than the coefficient of friction of the electroplated tin finish on nickel-plated phosphor bronze, which is greater than 0.7 to about 0.9.

[0058] The reflowed SAC finish was further evaluated against a hot dip tin finish. In the hot dip Sn finish, the hot dip tin, which was nearly completely intermetallic converted, exhibited a very low coefficient of friction of 0.15 to 0.3. This further indicates that the gravure printed and reflowed SAC was not completely converted to a copper-tin based intermetallic compound. Instead, the surface finish 20 exhibits free tin particles. This is particularly advantageous when the surface finish 20 is applied to the crimp area of ​​the electrical conductor 1.

[0059] Contact resistance performance measurements were made using 2.5 μm thick electroplated gold on a 1.5 mm radius AgNi probe. Contact resistance was measured at incremental loads from 0 to 5 N. Reflowed SAC finishes were compared to hot-dip tin and bare copper. Due to the high normal force required to break the copper surface film, the contact resistance of bare copper was much higher compared to the contact resistance of the tin finish. The static contact resistance of the reflowed SAC finish is similar to that of hot-dip tin.

[0060] Overall, the test results showed that gravure printing and reflow produces a surface finish equivalent to that of a hot-dip galvanized surface finish. Gravure printing and reflow is more cost-effective and versatile, allowing for a variety of different surface finishes and / or patterns.

[0061] A top view of an exemplary embodiment of an electrical conductor 1 is shown in Figure 2. The electrical conductor 1 comprises a conductive substrate 2 having at least one region 10 of a predetermined size and / or shape that has been applied with a surface finish 20 by gravure printing and reflowing a printed ink that melts and solidifies into the surface finish.

[0062] In some embodiments, the substrate hardness (hardness measurements were performed using a micro Vickers hardness tester) is retained after induction heating. For example, the substrate hardness is at least about 90%, including at least 95%, of the original hardness. In other embodiments, the substrate hardness is altered after induction heating. For example, the substrate hardness is reduced to no more than about 40%, or 50%, or 80% of the original hardness. Retained or altered hardness can be achieved with different dwell times, temperatures, and temperature profiles for different applications.

[0063] As can be seen, a variety of different patterns can be printed by gravure, flexographic processes, or a combination of gravure and flexographic printing, all with high reliability and edge resolution. Different surface finishes can be formed in different areas. Preferably, a tin surface finish is formed in a first area and a silver surface finish is formed in a second area.

Claims

1. A method for forming a surface finish (20) on a conductive substrate (2), the method comprising: - transferring an ink (6) containing conductive particles (8) to areas of defined shape and / or size (10) on the surface (4) of said conductive substrate (2) by gravure printing and / or flexographic printing; - heating said ink (6) to a temperature above the melting point of said conductive particles (8) to produce a melt, which solidifies into said surface finish (20); Including, The method, wherein the ink (6) is heated by inductively heating the conductive substrate (2).

2. The method of claim 1 , wherein the conductive particles (8) comprise or consist of tin.

3. 2. The method of claim 1, wherein a first ink (6) comprising a first set of conductive particles (8) is transferred to a first area (10) of predetermined size and / or shape by gravure printing and / or flexographic printing, and a second ink comprising a second set of conductive particles is transferred to a second area of ​​predetermined size and / or shape, the materials of the first set of conductive particles (8) and the second set of conductive particles being different from each other.

4. 4. The method of claim 3, wherein the first ink (6) and the second ink are melted in a subsequent step.

5. 5. The method of claim 4, wherein the first ink (6) is melted by induction heating and the second ink is melted by electron beam melting.

6. The method according to claim 1, wherein the conductive particles (8) have an average particle size of between 2 μm and 5 μm.

7. The ink has a kinetic viscosity of 10 s at 25° C. -1 2. The method of claim 1, wherein the viscosity is less than 10 Pas as measured at 1000.degree.

8. The method of claim 1 , wherein the conductive particles have an oxygen content of less than 1 wt %.

9. The method described in claim 1, wherein the conductive substrate (2) is provided on an electrical conductor (1), and the conductive substrate (2) has a surface (4) including an area (10) of predetermined size and / or shape to which the surface finish (20) is applied.

10. 10. The method of claim 9, wherein a layered structure is formed in the region (10), the layered structure including an intermetallic phase and a layer of solid conductive particles (8).

11. The method of claim 10, wherein the layer of solid conductive particles (8) forms an upper layer of the surface finish (20).

12. The method of claim 9, wherein the edges of the surface finish (20) have a lateral resolution of less than 1 mm.

13. The method of claim 9, wherein the surface finish (20) has a predetermined thickness variation within the region (10).

14. The method of claim 9, wherein the surface finish (20) has a thickness of 0.75 to 5 micrometers.

15. The method of claim 9, wherein the surface finish (20) has between 0.01 wt % and 0.5 wt % organic material.

16. The method of claim 9, wherein the surface finish (20) has a grain structure on an upper surface.

Citation Information

Patent Citations

  • Method for manufacturing at least one functional region on an electrical contact component such as a switch contact or plug contact.

    JP2014516384A

  • Methods of soldering and applications thereof

    US10470314B1

  • Ultrasonic consolidation of particulates in ink for functional coatings

    US20210129181A1